Domestic Revenue Mobilization and Agricultural Productivity: Evidence from Nigeria - POPOOLA, Olabisi; ASALEYE, Abiola John; ELUYELA, Damilola Felix (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).31, 2018)
Foreign and domestic debts have raised questions about fiscal sustainability and implications for sustainable development. One of the major problems in the agricultural sector in developing economies is inadequate capital, despite its centrality to growth and development. This study examines the long-run relationship and the casual relationships between domestic revenue mobilization and agricultural productivity in Nigeria using Auto Regressive Distributed Lag and Granger Non-causality. Using agricultural productivity as the dependent variable, the result revealed that agricultural productivity has a negative long-run relationship with government recurrent expenditure on agriculture and tax revenue, while agricultural credit is not statistically significant. This result indicated that supplementary resource such as foreign aid could be embarked on in the long-run. Reliance on foreign aid may be volatile to the economy, and as well not suitable to achieve long-term goals. So, there is a need to maximize benefit from tax revenue and ensure that resources are allocated to prioritizes right sectors such as the agricultural sector. The causality test revealed that there is a bi-directional relationship between agricultural productivity and tax revenue. The study recommended among others, the need for public finance reforms to increase government revenue and promote growth in the agricultural sector by enhancing the quality of the tax system.